Perencanaan Hidrolis Pintu Pada Bangunan Pengambilan Air (Intake) - Silitonga, Binsar; Hendry, Hendry (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2018)
The planning process of an intake water building must be conducted properly, such by considering several aspects namely topography, hydro-climatology, and also hydraulic condition of existing stream. In the planning of intake water building, the dimensions of water gate are based on the existing weir building. The Existing Dam building in this study is Sei Bingei weir. This weir was constructed to detain the flow of Bingei River. The weir is used to collect water to fill the demand of water company (PAM) Tirta Sari Binjai City.